PENGARUH DEFERRED TAX DAN TAX TO BOOK RATIO TERHADAP KINERJA KEUANGAN - Hani, Syafrida; Nadhira, Retno Asti; Irfan, Irfan (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
The difference in recognition of income and expenses according to SFAS and tax policies causes the need to present deferred tax information on the balance sheet and fiscal reconciliation to determine tax expense. The test results found that deffered tax and tax to book ratio have a negative effect on return on equity. Return on equity (ROE), as the information needed by investors on the ability to return to manage equity, will decrease if the deffered tax and tax to book ratio increase. If the tax to book ratio is low, it shows a low tax burden, so that it will be able to improve ROE performance. The ability of these two variables affects the return on equity by 22.2%